2001
DOI: 10.1054/bjoc.2001.1731
|View full text |Cite
|
Sign up to set email alerts
|

Dacarbazine and interferon α with or without interleukin 2 in metastatic melanoma: a randomized phase III multicentre trial of the Dermatologic Cooperative Oncology Group (DeCOG)

Abstract: In several phase II-trials encouraging tumour responses rates in advanced metastatic melanoma (stage IV; AJCC-classification) have been reported for the application of biochemotherapy containing interleukin 2. This study was designed to compare the efficacy of therapy with dacarbazine (DTIC) and interferon α (IFN-α) only to that of therapy with DTIC and IFN-α with the addition of interleukin 2 (IL-2) in terms of the overall survival time and rate of objective remissions and to provide an elaborated toxicity pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 22 publications
(23 reference statements)
0
32
0
8
Order By: Relevance
“…The contribution of biotherapy including IL-2 to the efficacy of biochemotherapy has been evaluated in several Phase III trials. These trials varied in sample size, choice of chemotherapy regimen, dose schedule of IL-2, and choice of control arm (Khayat et al, 1993;Johnston et al, 1998;Rosenberg et al, 1999;Hauschild et al, 2001;Atzpodien et al, 2002;Eton et al, 2002;Atkins et al, 2003;Keilholz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The contribution of biotherapy including IL-2 to the efficacy of biochemotherapy has been evaluated in several Phase III trials. These trials varied in sample size, choice of chemotherapy regimen, dose schedule of IL-2, and choice of control arm (Khayat et al, 1993;Johnston et al, 1998;Rosenberg et al, 1999;Hauschild et al, 2001;Atzpodien et al, 2002;Eton et al, 2002;Atkins et al, 2003;Keilholz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In three prospectively randomized trials, patients received BCDT (dacarbazine, cisplatin, carmustine, tamoxifen [BCDT]) regimen with or without IL-2, the response rates and survival duration of the patients treated with either regimen were similar (Johnston et al, 1998;Hauschild et al, 2001;Keilholz et al, 2005). Keilholz et al (2005) reported on a Phase III trial involving 362 patients with metastatic melanoma who were randomized to receive the dacarbazine, cisplatin, and IFNα combination alone or with IL-2 (Atzpodien et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nine eligible trials, six compared various regimens of chemotherapy with biochemotherapy 4-9 , two compared chemotherapy plus IFN with biochemotherapy 10,11 , and one trial compared biochemotherapy with a combination of IFN and IL-2 12 . Dose and method of administration varied from trial to trial.…”
Section: Resultsmentioning
confidence: 99%